You Are What You Eat: Affirming Podcast and Subjective Wellbeing among African American Women. (April 2022) - Robinson, Yatesha D.
The purpose of this exploratory study was to investigate whether intentional exposure to affirming messages via podcast would lead to improvement in subjective wellbeing in a sample of African American women. This two-part study used a mixed-methods design to measure subjective wellbeing using the Multicultural Quality of Life Index and a series of focus groups. During Phase 1, participants rated and discussed culturally relevant affirmations that informed the development of the podcast intervention used in Phase 2. The results revealed that stressors such as microaggressions, mental distress, and competing demands justified the need for support. Participants indicated that the podcast intervention was an enriching experience that illuminated the necessity of restorative practices that heal and revitalize the spirit. The intervention led to positive behavior change; and these results demonstrated the podcast benefits, suggesting that intentional exposure to positive messages may help some African American women cope with life stressors.